Association between apolipoprotein A‐IV concentrations and chronic kidney disease in two large population‐based cohorts: results from the KORA studies - Stangl, Stephanie; Krämer, Bernhard (Journal of internal medicine, 2015)
Abstract Background Apolipoprotein A?IV (apoA?IV) is an anti?atherogenic and antioxidative glycoprotein. Plasma apoA?IV levels are elevated in patients with primary chronic kidney disease (CKD) or renal failure. The association between apoA?IV and kidney function has not been investigated in the general population; therefore, we analysed this relationship in two large population?based cohorts. Methods Plasma apoA?IV concentrations were measured in the Cooperative Health Research in the Region of Augsburg (KORA) F3 (n = 3159) and KORA F4 (n = 3061) studies. CKD was defined by the serum creatinine?estimated glomerular filtration rate (eGFR) and/or urine albumin?to?creatinine ratio. Results Mean (±SD) apoA?IV concentration was 17.3 ± 4.7 mg dL?1 in KORA F3 and 15.3 ± 4.3 mg dL?1 in KORA F4. Fully adjusted linear mixed models revealed a significant association between apoA?IV concentration and lower eGFR in the third and fourth versus the first quartile of apoA?IV (? = ?1.78 mL min?1/1.73 m², P = 0.0003 and ? = ?5.09 mL min?1/1.73 m², P = 2.83 ? 10?23, respectively). ApoA?IV was significantly associated with an eGFR of <60 mL min?1/1.73 m², which was observed in 601 of the 6220 study participants [odds ratio (OR) 1.46, P = 0.03 and OR 3.47, P = 6.84 ? 10?15 for the third and fourth vs. the first quartile of apoA?IV, respectively]. Adding apoA?IV (fourth vs. first quartile) to the fully adjusted model significantly improved discrimination of eGFR <60 mL min?1/1.73 m² in KORA F3 [integrated discrimination improvement (IDI) 0.03, P = 1.30 ? 10?7] and KORA F4 (IDI 0.04, P = 1.32 ? 10?9) beyond classical risk factors for CKD. Conclusion The present analysis in two population?based cohorts revealed that high plasma apoA?IV concentrations are strongly associated with low kidney function defined by eGFR independent of major CKD risk factors. ApoA?IV appears to be an early marker of impaired kidney function.